Animal sacrifice, religion and law in South Asia - Berti, Daniela; Good, Anthony (Routledge religion in contemporary Asia series, 2024)
"This book presents original research on the controversies surrounding animal sacrifice in South Asia through the lens of court cases. It focuses on the parties involved in these cases: on their discourse, motivations, and contrasting points of view. Through an examination of judicial files, court decisions and newspaper articles, and interviews with protagonists, the book explores how the question of animal sacrifice is dealt with through administrative, legislative, and judicial practice. It outlines how although animal sacrifice has over the ages been contested by various religious reform movements the practice has remained widespread at all levels of society, especially in certain regions. It reveals that far from merely being a religious and ritual question, animal sacrifice has become a focus of broader public debate, and it discusses how the controversies highlight the contrast between 'traditional' and 'reformist' understandings of Hinduism; the conflict between the core legal and moral principles of religious freedom and social progress; and the growing concern with environmental issues and animal rights"--